Social Problems in India: An Analytical Study (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Social problems are significant issues that affect a large portion of the population and deviate from established social norms. Since gaining independence from British rule in 1947, India has faced a variety of social challenges that impact its development and the quality of life of its citizens. This article explores some of the most pressing social problems in India, including poverty, unemployment, overpopulation, child labor, the dowry system, crimes against women, pollution, mental health, corruption, political instability, the caste system, the role of non-governmental organizations (NGOs), government schemes, and the importance of research in addressing these issues.